Enhancing higher education student well-being through social prescribing: a realist evaluation protocol - Mark Davies; Sarah Wallace; Carolyn Wallace; David Pontin; Megan Elliott (BMJ Open, 2022)
Introduction UK higher education (HE) student numbers are increasing and students report higher levels of mental health and well-being issues. Social prescribing links individuals to community-based, non-medical support. It is widely implemented throughout the UK, and is supported by the Welsh Government. This protocol presents an evaluation of a new social prescribing service to enhance student well-being, a first for UK HE students.Methods and analysis A realist evaluation to articulate why, how and to what extent and circumstances social prescribing works for students, using a mixed-methods sequential design of four cycles. Cycle 1 informs the model and programme theory development of how the model works; activities include a Realist Review, Group Concept Mapping and producing bilingual short films about the evaluation and model. Cycle 2 involves secondary analysis of routine service data, and outcome measurements from students receiving a social prescription. Cycle 3 uses reflective diaries and qualitative realist interviews with stakeholders to understand the process and outcome of the model. Cycle 4 concludes with a world café workshop with stakeholders to agree and finalise the framework specification of ‘how, why, when and to what extent’ the model works. A meta-matrix construction will determine convergence, complementarity or discrepancy across the cycles. An advisory group of key stakeholders informs each cycle.Ethics and dissemination University of South Wales Life Sciences and Education Ethics Committee and Wrexham Glyndwr University (WGU) Research Ethics Sub-Committee approved secondary data analysis of participant demographics (200 805LRL:USW, id441:WGU), outcome measurement tools (200 902LR:USW, id441:WGU) and qualitative data collection (200 804LR:USW, id449:WGU). The authors will publish findings in peer-reviewed journals, produce an evaluation report to the funder and a short film for dissemination via stakeholders, university networks, United Nations Regional Centre of Expertise in Wales, PRIME Centre Wales, Wales School for Social Prescribing Research, conferences and social media.